PARANOIA AND SADISM OF THE INSTITUTION. ON WITOLD GOMBROWICZ´S “BANQUET AT COUNTESS KOTŁUBAJ´S” - Warkocki, Błażej (Porównania, 2018)
The article offers a close reading of Witold Gombrowicz’s short story Banquet at Countess Kotłubaj’s from his debut collection Memoirs from a Time of Immaturity (later published under the title Bakakaj or Bacacay in the English translation). It is based on two theoretical concepts: on the one hand – a paranoid plot (according to Eve Kosofsky Sedgwick 2014), on the other hand – sadism (as non-complementary to masochism) in the sense of Gilles Deleuze (from his essay Coldness and cruelty). The author is looking for social subversion in the grotesque images of class and finds it in the sadism of the institution of aristocracy which moves the main character into a paranoid position.